2014
DOI: 10.3171/2014.7.peds13563
|View full text |Cite
|
Sign up to set email alerts
|

Number and location of draining veins in pediatric arteriovenous malformations: association with hemorrhage

Abstract: Object The significance of draining vein anatomy is poorly defined in pediatric arteriovenous malformations (AVMs). In adult cohorts, the presence of fewer veins has been shown to lead to an increased rate of hemorrhage, but this phenomenon has not yet been studied in pediatric AVMs. This report analyzes the impact of draining vein anatomy on presentation and outcome in a large series of pediatric AVMs. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…[24][25][26][27][28] Most of these factors and results were obtained from a retrospective cohort (younger than 22 years of age) at Columbia University Medical Center. 24,26,28 Two larger studies reported results with a relatively distinct bias (a wide range of odds ratio or only radiosurgery patients), suggesting that these studies might have been underpowered to assess the impact of certain features on BAVM hemorrhage.…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…[24][25][26][27][28] Most of these factors and results were obtained from a retrospective cohort (younger than 22 years of age) at Columbia University Medical Center. 24,26,28 Two larger studies reported results with a relatively distinct bias (a wide range of odds ratio or only radiosurgery patients), suggesting that these studies might have been underpowered to assess the impact of certain features on BAVM hemorrhage.…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientsmentioning
confidence: 99%
“…[24][25][26][27][28] Most of these factors and results were obtained from a retrospective cohort (younger than 22 years of age) at Columbia University Medical Center. 24,26,28 Two larger studies reported results with a relatively distinct bias (a wide range of odds ratio or only radiosurgery patients), suggesting that these studies might have been underpowered to assess the impact of certain features on BAVM hemorrhage. 25,27 In this exclusively pediatric cohort (18 years old or younger) of patients with BAVMs referred to a high-volume Chinese neurosurgery center during the past 5 years, we identified periventricular nidus location and smaller nidus size as independent predictors of hemorrhagic presentation.…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuroimaging is the preferred method of diagnosis after high clinical suspicion of MMD or MMS. Intracranial hemorrhage and cerebral infarction can be diagnosed with computed tomography and magnetic resonance imaging/ cerebral angiogram, respectively (8,9). Recent use of magnetic resonance perfusion imaging has been shown to be crucial in diagnostics and medicalsurgical decision making.…”
mentioning
confidence: 99%